Effect of intraoperative goal-directed fluid therapy on the postoperative brain edema in patients undergoing high-grade glioma resections: a study protocol of randomized control trial - Liu, Xiaoyuan; Zhang, Xingyue; Fan, Yifang; Li, Shu; Peng, Yuming (Current controlled trials in cardiovascular medicine, 2022)
Introduction Brain edema is the most frequent postoperative complication after brain tumor resection, especially in patients with high-grade glioma. However, the effect of SVV-based goal-directed fluid therapy (GDFT) on postoperative brain edema and the prognosis remain unclear. Methods and analysis This is a prospective, randomized, double-blinded, parallel-controlled trial aiming to observe whether stroke volume variation (SVV)-based GDFT could improve the postoperative brain edema in patients undergoing supratentorial high-grade gliomas compared with traditional fluid therapy. The patient will be given 3 ml/kg hydroxyethyl starch solution when the SVV is greater than 15% continuously for more than 5 min intraoperatively. The primary outcome will be postoperative cerebral edema volume on brain CT within 24 h. Ethics and dissemination This trial has been registered at ClinicalTrials.gov (NCT03323580) and approved by the Ethics Committee of Beijing Tiantan Hospital, Capital Medical University (reference number: KY2017-067-02). The findings will be disseminated in peer-reviewed journals and presented at national or international conferences relevant to the subject fields. Trial registration ClinicalTrials.gov NCT03323580 (First posted: October 27, 2017; Last update posted: February 11, 2022).